A review of pregnancy information on nutrition, physical activity and sleep websites. Issue 1 (February 2020) - Cannon, Summer; Lastella, Michele; Vincze, Lisa; Vandelanotte, Corneel; Hayman, Melanie
Abstract: Problem: Most pregnant women report using the internet to source health information during pregnancy. However, little is known about the information presented on the internet and whether it is consistent with current evidence-based guidelines. Background: Pregnancy is considered a risk period for women as it is associated with poorer health behaviours including an inadequate diet, decreased physical activity and reduced sleep. As a result, pregnant women and their unborn child are at a greater risk of adverse health outcomes. Aim: The purpose of this study was to review pregnancy related information about nutrition, physical activity and sleep provided on Australian government and leading industry body websites, and to compare this information to current evidence-based guidelines. Methods: A systematic online search was conducted to identify Australian Government, and leading industry websites that provided information on nutrition, physical activity, or sleep during pregnancy. The content of each website was reviewed and compared against current nutrition, physical activity and sleep guidelines. Findings: 27 government and leading industry websites were included in this study. 18 websites included nutritional information, none of which aligned 100% with guidelines. Nine websites included physical activity information, only one of which was 100% in accordance with guidelines. Two websites included information on sleep during pregnancy, however neither were in accordance with guidelines. Conclusion: Women are accessing information via the internet that is not in accordance with current evidence-based guidelines. These results call to attention the need for government and leading industry websites to review and update their website information in accordance with current evidence-based guidelines.